Tax evasion - The behavioral background - Darák, Péter; Gyekiczky, Tamás; Lovas, Dóra; Somogyi, Róbert (Public Finance Quarterly, 2024)
Our research aimed to explore the “black box” of taxpayers’ decision-making in an attempt to identify generalizable patterns of behaviour. The analysis was based on the published decisions of the Curia from 2018 to 2023. The information from the judgments was transferred into the statistical data processing system, creating 39 variables. The variables and their correlations were analyzed using the statistical program SPSS. The statistical sample included 120 review judgments, which were representative of the review cases of the period. In addition to the statistical empirical evidence, our study processed models from the literature on tax avoidance and reconstructed individual tax rate positions.